PENGEMBANGAN MODEL PEMBELAJARAN GERAK DASAR LOMPAT DENGAN PERMAINAN SUMBAR (SUSUN GAMBAR) PADA SISWA KELAS II SD NEGERI SUMBEREJO 02 KEC. PABELAN KAB. SEMARANG TAHUN 2013 - Ricky Prakoso; Anirotul Qori'ah (Universitas Negeri Semarang, 2015)
The purpose of this study is to produce a model of learning basic movement jump through games sumbar (stacking images) that can help teachers and students in learning penjasorkes. This study uses a method which is the basis for the development as for the procedures / steps are as follows: (1) to analyze the product to be developed; (2) developing initial products; (3) expert validation and revision; (4) small group testing and revision of the product; (5) field testing and final product; (6) revision of the final product; and (7) the outcome boast a game modification (stacking images) were generated through field trials revision. From the test results obtained penjas learning expert evaluation data, from both experts stated that the development of models already boast a game in the category of good judgment. However, there needs to be repaired, because there are few alternative answers are still pretty good claim. The trial of small group 92.8% (very good), and field trials 93.6% (very good). From these results it can be concluded models game sumbar (stacking images) for learning basic movement jump fit for use.